ACCESSING FUNDING AND PROBLEMS OF COMMUNITY ENTERPRISE ENTREPRENEURS IN PHRA NAKHON SI AYUTTHAYA PROVINCE - Sastsara , Sasinan; Mekdee, Kobchai (Journal of Educational Review Faculty of Education in MCU, 2021)
The objectives of this research are 1) to study the sources of problems in accessing funding sources and solutions for accessing funding sources of community enterprise entrepreneurs in Phra Nakhon Si Ayutthaya province; 2) to compare the problem factors in accessing funding sources of community enterprise entrepreneurs in Phra Nakhon Si Ayutthaya province classified by sources of funding and 3) to study the relationship between problems in accessing funding sources and solutions to problems accessing funding sources of community enterprise entrepreneurs in Phra Nakhon Si Ayutthaya province. This research deployed mixed research method with the use of questionnaires and interviews as research tools. The sample group consisted of 232 community enterprises, 4 government agencies and financial institutions. The statistics used in the data analysis were one-way ANOVA analysis and Pearson’s correlation coefficient. The results of the research revealed that 1) Problems in accessing funding sources are the lack of knowledge and understanding of the terms of lending from financial institutions and the unclear accounting system that purpose of the loan is not clearly defined. The solution to the problems are building an understanding of loan terms and enhancing management skills writing a business plan; 2) Comparison of problem factors in accessing funding sources in case of using self-funding in different proportions have significant differences in accessing funding sources at the statistical level of 0.05, loans from different sources in different proportions have statistically significantly different in access to funding problems at the level of 0.05, Entrepreneurs who used to borrow money from the informal system and those who have never borrowed money outside the system have different problems in accessing funding sources with statistical significance at the level of 0.05; 3) The relationship between accessing funding problems and solutions found that problems in accessing funding sources were related to solutions for accessing funding.